The Influence of Flash Sale on Impulsive Buying Behavior Through the Shopee E-Commerce Application in PIPS FKIP University of Riau Students - Erlina Manurung; Sri Kartikowati; Hendripides Hendripides (CV. Rayyan Dwi Bharata, 2024)
The purpose of this study is to analyze the effect of flash sales on impulse buying behavior through the Shopee e-commerce application with the target of 126 students majoring in PIPS FKIP Universitas Riau class of 2021 as a research sample determined based on purposive sampling techniques. By using quantitative descriptive methods. The data were collected using a questionnaire instrument and analyzed with the T test. The results obtained were 0.000 α 0.05, so it can be concluded that there is a positive and partially significant influence between partial flash sales on impulse buying behavior in students majoring in PIPS FKIP Riau University.